2004
DOI: 10.1056/nejmoa040125
|View full text |Cite
|
Sign up to set email alerts
|

Palifermin for Oral Mucositis after Intensive Therapy for Hematologic Cancers

Abstract: Palifermin reduced the duration and severity of oral mucositis after intensive chemotherapy and radiotherapy for hematologic cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
531
6
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 789 publications
(570 citation statements)
references
References 28 publications
(20 reference statements)
19
531
6
14
Order By: Relevance
“…The Food and Drug Administration approved the use of KGF for chemotherapy-induced mucositis in December of 2004 (39). Clinical trials with KGF demonstrated reduced duration of oral lesions and salivary gland toxicity in patients with head and neck cancers treated with chemoradiation, diminished duration and severity of mucositis during bone marrow transplantation conditioning, and reduced incidence and severity of mucositis after chemotherapy for metastatic colorectal carcinoma (reviewed by Barasch et al (40).…”
Section: Discussionmentioning
confidence: 99%
“…The Food and Drug Administration approved the use of KGF for chemotherapy-induced mucositis in December of 2004 (39). Clinical trials with KGF demonstrated reduced duration of oral lesions and salivary gland toxicity in patients with head and neck cancers treated with chemoradiation, diminished duration and severity of mucositis during bone marrow transplantation conditioning, and reduced incidence and severity of mucositis after chemotherapy for metastatic colorectal carcinoma (reviewed by Barasch et al (40).…”
Section: Discussionmentioning
confidence: 99%
“…KGF has been shown to be a protective factor for oral mucositis in randomized clinical trial in patients with autologous HSCT [59]. It is currently in clinical trials to assess its effects on GVHD, mucositis and T cell reconstitution in HSCT recipients.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…For survivors only to day 90 (n=42), the duration of ventilation was increased in the KGF group (16 [13-30] versus 11 [8][9][10][11][12][13][14][15][16] days; P = 0路002). In addition, in the KGF group compared to the placebo group the duration of ICU stay (22 [14-34] versus 12 [10][11][12][13][14][15][16][17][18][19] days; P = 0路001) and hospital stay (Table 4) were also increased From randomization to day 90, the probability of survival (online supplement Figure e1a) or breathing without assistance (online supplement Figure e1b) was higher in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference between the two groups in OI at day 7 (the primary outcome) or in any other secondary physiological outcomes. The KGF group, compared to placebo, had fewer median ventilatorfree days (1 [0-17] versus 20 [13][14][15][16][17][18][19][20][21][22] days; difference -8 days, 95% CI -17--2; P < 0路001), a longer median duration of ventilation in survivors (16 [13-30] versus 11 [8][9][10][11][12][13][14][15][16] days; difference 6 days, 95% CI 2-14; P = 0路002) and a higher mortality at 28 days (31路0% versus 9路7%; risk ratio 3路2 95% CI 1路0-10路7; P = 0路054).…”
Section: Disseminationmentioning
confidence: 99%
See 1 more Smart Citation